REGRESSION MODELS OF THE UPPER RESPIRATORY AREA IN YOUNG WOMEN AND YOUNG MEN WITHOUT AND TAKING INTO ACCOUNT THE TYPE OF FACE IN DEPENDENCE ON TELEROENTGENOMETRIC INDICES - Kostiuchenko-Faifor, O.S.; Gunas, I.V. (World of Medicine and Biology, 2023)
In Ukrainian young women and young men with an orthognathic bite without and taking into account the type of face, reliable (p
Keywords: teleroentgenography; cephalometry; respiratory tract; modeling; young men; young women; orthognathic bite; facial types